APLIKASI DIGITAL PERMUDAH KEBUTUHAN GEN Z (STUDI EKONOMI NETNOGRAFI) - Putri, Sri Andika; Sulistiyowati, Yayuk (Unitri Press, 2024)
The COVID-19 pandemic is one of the reasons for the accelerated use of digital technology. The usage of these platforms has permeated all strata of society. New students, who make up more than 50% of university enrolees, often come from regions outside their place of study. To interact with their new surroundings, they must socialize and communicate with the local community. Unfortunately, not all new students are proficient in the local languages. The purpose of this research is to ascertain the extent to which digital applications are utilized by new students to meet their daily needs. The method employed in this research is Netnography, utilizing questionnaires and interviews. Questionnaires and interviews were conducted with new students from outside the Java Island, specifically from the eastern regions of Indonesia, who are studying at Tribhuwana Tunggadewi University. Interviews were conducted to identify communication barriers faced by students upon relocating from their hometowns. A questionnaire in the form of a Google Form was distributed to determine which digital applications are frequently used to assist in meeting their needs. The research findings indicate that new students communicate in Indonesian. However, the use of Indonesian sometimes leads to misunderstandings with local residents due to differences in intonation and accent from their regions of origin. To simplify the fulfilment of their needs, they prefer using digital applications, choosing based on specific needs and price comparisons. Digital applications have proven to facilitate students in meeting their daily needs, especially during the initial period after arriving from their hometowns.